THE ROLE OF THE RENTAL DISPUTE CENTER ON THE RENTAL SECTOR IN DUBAI AN ANALYTICAL OVERVIEW - Sanna, Ahmed Ibrahem (South Asian Journal of Social Sciences and Humanities, 2023)
The rental sector in the UAE represents about half of the real estate sector, as it is one of the basics on which the economy is based and one of the essential basic pillars in the economic sector. Due to that, the local legislator intervened in the Emirate of Dubai to achieve transparency in this sector and protect dealers’ rights. Therefore, the government established a Rental Dispute Center Dubai (RDCA) to resolve rental disputes arising between the parties from the rental contract. In this regard, the article examines the extent of the contribution of the RDCA to the development of the real estate sector and the provision of a safe and stable environment for investors on the one hand and for the parties to the rental relationship on the other. The article adopted the social legal research methodology. The data were examined using an analytical and critical approach. It found that the RDCA has been demonstrated to effectively accomplish simplicity, expediency, and efficiency in resolving rental disputes, thereby distinguishing itself from the judicial system. It also has significantly contributed to safeguarding the rights of all involved parties within the rental relationship, thereby augmenting the growth and advancement of the real estate sector. However, the article recommends that certain legal provisions that appear to contradict the principle of judicial independence be revised in order to fully realise the goals for which the RDCA was established.
Keywords: Rental Dispute Settlement Center; Rental Sector; UAE; Dispute Settlement